Spectroscopic properties of Er3+ in oxysulfide glasses - Vila, L. D.; Aranha, N.; Messaddeq, Younes [UNESP]; Stucchi, Elizabeth Berwerth [UNESP]; Ribeiro, S.; Fagundes, D.; Nunes, LAO (Elsevier B.V., 2002)
Er3+ -containing gallium-lanthanum oxysulfide glasses have been prepared from Ga2O3 and La2S3 in a sulfur/argon reactive atmosphere. The samples have been characterized by absorption and emission spectroscopy and IR emission kinetics. Er3+ electronic transition intensities have been analyzed in the light of the Judd-Ofelt formalism, and quantum efficiencies evaluated for the Er3+ emission at 1.5 and 2.7 mum. The results so obtained suggest that these glasses display favorable properties concerning IR optical applications. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: oxysulfide glasses; erbium; IR emission